From the issues of national policy in the First Czechoslovak Republic – the dispute over the national identity of the Transcarpathian Rusyns - Bruski , Jan Jacek (Balcanica Posnaniensia. Acta et studia, 2001)
The article is devoted to the problem of the national identity of the Ruthenians inhabiting Subcarpathian Rus’ during the interwar period and to the position of the Czechoslovak authorities toward this issue. The author aims to analyze national disputes among the Ruthenians and to demonstrate their significance for the nationality policy of the First Czechoslovak Republic. The study is based on the analysis of political documents, legal acts, and the activities of socio-cultural organizations in Transcarpathia. The author points out that the incorporation of Subcarpathian Rus’ into Czechoslovakia was initially regarded as a temporary solution. Despite promises of autonomy, the authorities in Prague gradually limited the possibility of its implementation, citing the region’s political immaturity and the threat posed by Hungarian irredentism. The article examines the rivalry among three national orientations: Ukrainian, Russian, and Ruthenian. Supporters of the Ukrainian orientation sought to identify the Ruthenians as part of the Ukrainian nation; advocates of the Russian orientation viewed them as part of the Russian nation; while the third group argued for the existence of a distinct Carpatho-Ruthenian nation. The conclusions indicate that the dispute over Ruthenian national identity was one of the key nationality problems of interwar Czechoslovakia and had a significant impact on relations between the state center and the peripheral region of Transcarpathia.